Validity and Reliability of Thai Version of the Overactive Bladder Questionnaire Short form (OAB-q SF) in Women with Overactive Bladder - Sangnucktham, Thanawat; Bunyavejchevin, Suvit; Ruanphoo, Purim (Thai Journal of Obstetrics and Gynaecology, 2024)
Objectives: To study the validity and reliability of Thai version of the OAB-q SF and the correlation of Thai version OAB-q SF to Thai version OAB-q. Materials and Methods: During December 2017 to February 2018, after IRB approvement, 46 Thai patients diagnosed as having OAB attending a Female Pelvic Medicine and Reconstructive Surgery clinic at King Chulalongkorn Memorial hospital were recruited. Patients’ characteristics were recorded. The self- answered, Thai version of the OAB-q SF was administered on two occasions, at the day of recruitment and at 2 weeks apart (by mail). Thai version of OAB-q was administered only at the first visit. Results: Mean ± standard deviation of age was 65.63 ± 11.64 years, and their mean body mass index (BMI=-0987 was 26.25 ± 8.13 kg/m2. Most women were treated for OAB more than 6 months (47.9%). Behavioral modification was used to treat in all patients. Oral medication was administered in 54.35% of patients. Cronbach’s alpha of the OAB-q SF was 0.80 and 0.93 for symptom-bother and HRQL domains, respectively. The ICCr of symptom bother scale and HRQL were 0.90 and 0.94. The content validity index was equal to 1. Pearson correlation of the total score of the OAB-q SF and OAB-q was 0.95 for the first visit questionnaire. Conclusion: Thai version of the OAB-q SF showed good psychometric properties (reliability and validity) for measuring the OAB symptom severity and HRQL. There was very strong correlation between Thai version of OAB-q SF and OAB-q.